The Economic Chambers and the Enforcement of Local Economic Interests - Póla, Péter (Discussion Papers, 2012)
A detailed analysis of the institutional system of chambers with the presentation of their essential features is of fundamental importance not only because the introduction of the basic concepts of the institutional system is an integral part of this dissertation but also because contemporary Hun¬garian society has very limited information on the institutional system of cham¬bers. In the present study the Author is attempting to de¬scribe the role of chambers within the institutional system of the organisation of economy and to outline the general philosophy of chambers with pointing out to the difference between chambers and the institutions of the intermediary sphere. The first section is an overview of the different levels of the organisa¬tion of economy and of the relationship between them. This is followed by a review of literature on different groups of economic interest and an introduction of the general features of interest representation and trade associations, and finally a description of the legal status of chambers. The specific features of chambers origi¬nating from their public body and local governmental functions will also be analysed, focussing on their special tasks and roles. Through the examination of the legal status of chambers the Author strives to present a more detailed analysis on a public law based chambers. The final section is a comparison of the two basic - public and civil law - mod¬els of chambers with their characteristic features and a presentation of their advantages, disadvantages and the theoretical and practical problems aris¬ing from their growing discrepancy from the public law model in Hungarian legal regulation.